2020
DOI: 10.1101/2020.01.10.901579
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mitogen-activated protein kinase activity drives cell trajectories in colorectal cancer

Abstract: In colorectal cancer, oncogenic mutations transform a hierarchically organized and homeostatic epithelium into invasive cancer tissue. To define differences in cellular composition between the normal colon and colorectal cancer, and to map potential cellular interactions between tumor cells and their microenvironment, we profiled transcriptomes of >50,000 single cells from tumors and matched normal tissues of eight colorectal cancer patients. We find that tumor formation is accompanied by changes in epithelial… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Our finding that BRAF mutant CRC cell lines maintain high levels of EEC progenitors suggests the cell lines may provide suitable models for the study of secretory cells in progenitor states. When comparing our scRNA-seq data from HT29 and H508 cell lines to a normal human colon sample, multiple of the clearly defined cell types seen in the colon sample appeared in a more undifferentiated or transcriptionally altered state in the CRC cell lines, consistent with other studies of CRC tumors at single-cell resolution (Uhlitz et al, 2020). However, distinct cell types such as goblet cells and putative early EECs appeared well-defined and with clearly conserved markers in both the normal colon and CRC cell lines.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Our finding that BRAF mutant CRC cell lines maintain high levels of EEC progenitors suggests the cell lines may provide suitable models for the study of secretory cells in progenitor states. When comparing our scRNA-seq data from HT29 and H508 cell lines to a normal human colon sample, multiple of the clearly defined cell types seen in the colon sample appeared in a more undifferentiated or transcriptionally altered state in the CRC cell lines, consistent with other studies of CRC tumors at single-cell resolution (Uhlitz et al, 2020). However, distinct cell types such as goblet cells and putative early EECs appeared well-defined and with clearly conserved markers in both the normal colon and CRC cell lines.…”
Section: Discussionsupporting
confidence: 85%
“…Aggressive subtypes of NETs include those with goblet cell differentiation (goblet cell carcinoids) (McGory et al, 2005), and poorly differentiated NETs (PDNETs) (Basturk et al, 2014). While distinct from mucinous tumors, goblet cell carcinoids are pathologically more similar to adenocarcinomas of the large intestine than to other NET subtypes (van Eeden et al, 2007), which may contribute to their under-characterization in the large intestine due to the difficulty in differentiating them from canonical adenocarcinomas. However, recent pathological studies have begun to identify tumors similar to goblet cell carcinoids in the large intestine (Inoue et al, 2020) (Abdalla et al, 2020), indicating that mixed secretory lineage CRCs form at some previously unappreciated frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The latter indicated that angiocrine activities in the colon may trigger the course of diseases in a microenvironment–dependent manner. A recent single cell RNAseq approach of intestinal cells and subsequent bioinformatics interaction analyses supported the molecular interaction between endothelial cells and epithelial cells in the colon ( 121 ).…”
Section: The Impact Of Angiocrine Signaling On Epithelial Barrier Function In Ibdmentioning
confidence: 99%
“…An interesting avenue for future research lies in comparing healthy with tumoural intestinal tissue to clarify, whether one indeed observes similar cellular subpopulations and differen-tiation gradients. Recent research indeed suggests this [49,50]. Tracking the numbers of different cell types over time during development and after perturbations could therefore be expected to yield data for validating and parametrising the presented model.…”
Section: Differences In Relaxation Dynamics Of Different Model Topologies After Perturbationsmentioning
confidence: 85%